2015
DOI: 10.1111/nuf.12119
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making in Nursing Practice: A Concept Analysis

Abstract: Decision making in the nurse practice environment is a dynamic conceptual process that may affect patient outcomes. Nurses need to call upon ways of knowing to make sound decisions and should be self-reflective in order to develop the process further in the professional arena. The need for further research is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
122
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(149 citation statements)
references
References 52 publications
0
122
0
17
Order By: Relevance
“…In congruence with these present study findings, [26] in a study in Lebanese, found that Nurses were reported moderate levels of burnout. As well as, findings of Lin et al [27] showed moderate levels of Emotional Exhaustion and Personal Accomplishment, and low levels Depersonalization.…”
Section: Discussionmentioning
confidence: 84%
“…In congruence with these present study findings, [26] in a study in Lebanese, found that Nurses were reported moderate levels of burnout. As well as, findings of Lin et al [27] showed moderate levels of Emotional Exhaustion and Personal Accomplishment, and low levels Depersonalization.…”
Section: Discussionmentioning
confidence: 84%
“…Decision-making by nurses is a complex, dynamic and inseparable process of their training; its commitment is considering factors that, when combined, potentiate the quality of the decision and can affect the patient's prognosis and safety; these being: psychological, cognitive, and analytical aspects, information, situations and intuition 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Adapted from “Model of Decision Making” by Johansen and O’Brien (2016) [Copyright 2015 by John Wiley & Sons] with a superimposed socio-ecological lens (McLeroy et al, 1988). …”
Section: Figurementioning
confidence: 99%
“…To guide this study, a model of decision-making (Johansen & O’Brien, 2016) was adapted and superimposed with a socio-ecological lens (McLeroy, Bibeau, Steckler, & Glanz, 1988) that illustrates the contextual factors influencing visit plan development and implementation (see Figure 1). Decision-making is a cyclical and recursive process whereby decisions are reevaluated to be reaffirmed or replaced with other options by engaging in a new decision-making process (Johansen & O’Brien, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation